Investigation of DFNB4 SLC26A4 mutation in patients with enlarged vestibular aquaduct. (November 2020) - Kınoğlu, Kubilay; Orhan, Kadir Serkan; Kara, Hakan; Öztürk, Oğuz; Polat, Beldan; Aydoğan, Hülya; Çelik, Mehmet; Ceviz, Ayşe Begüm; Güldiken, Yahya
Abstract: Objectives: Mutations of the SLC26A4 gene causing enlarged vestibular aqueduct (EVA) syndrome have not yet been fully elucidated. The study aimed to investigate SLC26A4 mutations in patients with EVA syndrome in the Turkish population. Identifying these mutations may play an essential role in determining the prognosis, follow-up, and management options of these patients. Methods: Whole exome sequencing and/or Sanger sequencing of SLC26A4 in 22 patients with sensorineural hearing loss associated with isolated EVA without inner ear anomalies, and 22 controls were performed. Results: Twenty-two patients and 22 control subjects were included in the study. The onset of hearing loss was pre-lingual in 15 patients, and post-lingual in 7. The mean (standard deviation) vestibular aqueduct width of the patients was 3.23 mm (1.28). Twenty SLC26A4 variants, 15 of them unique, were identified in 22 patients. Among them, seven variants were heterozygous, and 13 were homozygous. The variants p.E37X (c.109G > T), p.Y27H (c.79T > C), p.C706Y (c.2117G > A) have not been previously reported. Conclusion: The detection of rare and previously unreported mutations in our study showed that studies with a larger number of patients with EVA might reveal more role of the SLC26A4 gene. Besides, to understand the etiopathogenesis of the disease, other related genes also should be investigated.